Monatomic catalyst taking oxygen-nitrogen co-doped hollow carbon nanocage as support carrier as well as preparation method and application of monatomic catalyst

By using the use of oxygen and nitrogen in a single atomic catalyst as a supporting carrier, and forming the M (N-C) 2 (N-O) 2 coordination structure, the existing catalysts in environmental interference and pH dependence are solved , Achieving the effect of efficient and stable toxic substances.

CN119368176APending Publication Date: 2025-01-28HUAZHONG NORMAL UNIV
View PDF 0 Cites 6 Cited by

Patent Information

Application Number
CN202311868658.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-31
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the advanced oxidation process, existing single-atom catalysts have problems such as sensitive environmental interference, strong pH dependence, and secondary pollution caused by the formation of free radical active substances, and the formation of high-valent metal oxygen species is difficult to achieve.

Method used

Using a single atomic catalyst with oxygen-nitrogen-nitrogen-nitrogen-mixed carbon nano cage as the support carrier, by mixing the transition metal metal hydrochloride, 1,10-Philippin, and SiO2@RF mixing Eclipse, forming a coordination structure of M (N-C) 2 (N-O) 2, improve the anti-environmental interference ability and the scope of pH applications of catalysts.

Benefits of technology

The high activity of catalysts, low metal dissolving rates, no secondary pollution, and extensive pH applicable range can efficiently remove various toxic substances, and the pollutants completely degrade within 30 seconds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004646362510000011
    Figure HDA0004646362510000011
  • Figure HDA0004646362510000012
    Figure HDA0004646362510000012
  • Figure HDA0004646362510000013
    Figure HDA0004646362510000013
Patent Text Reader

Abstract

The invention discloses a monatomic catalyst with an oxygen-nitrogen co-doped hollow carbon nanocage as a support carrier and a preparation method and application thereof. The monatomic catalyst comprises an oxygen-nitrogen co-doped hollow carbon nanocage carrier and a transition metal monatomic loaded on the carrier, the transition metal single atom is coordinated in the form of M (N-C) 2 (N-O) 2. Transition metal hydrochloride, 1, 10-phenanthroline monohydrate and silicon dioxide and resorcinol formaldehyde copolymer nanospheres with a core-shell structure are mixed and then subjected to a reflux reaction, rotary evaporation and drying are carried out, and an obtained solid is subjected to grinding, pyrolysis and etching to remove SiO2 to prepare the composite material. The monatomic catalyst is high in environmental interference resistance, wide in pH application range, high in activity and good in repeatability, and efficient removal of various toxic substances is achieved; the metal dissolution rate is low, and secondary pollution cannot be caused; the preparation process is simple, conditions are mild, and the method has wide industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalytic degradation of organic pollutants, and specifically relates to a single-atom catalyst using oxygen-nitrogen co-doped hollow carbon nanocages as a support carrier, and a preparation method and application thereof. Background Art

[0002] In recent years, single atom catalysts (SACs) with atomically dispersed metal active centers have been widely used in energy, environmental management and other fields because they make up for the problems of homogeneous catalysts being sensitive to the reaction environment and prone to secondary pollution, and heterogeneous catalysts having low metal atom utilization, poor catalytic activity, difficulty in determining the structure of active centers, and unclear catalytic mechanisms. Among them, in terms of advanced oxidation processes (AOPs), metal-based SACs can efficiently activate persulfate (PMS) and hydrogen peroxide (H2O2) to achieve the degradation of difficult-to-degrade organic pollutants in water. However, most SACs mainly produce SO4 by triggering the single-electron reduction of PMS. ·- and · OH and other free radical active substances. Free radicals are not only poorly resistant to interference from environmental media, but also highly dependent on pH values, and have low selectivity for various substances in wastewater. They can react with a large amount of Cl - Formation of low-reactivity, hazardous chlorinated byproducts (Cl2 ·- ), which hinders its practical application. To avoid the above problems, researchers have begun to focus on improving the degradation of organic pollutants through non-free radical pathways.

[0003] High-valent metal oxide (HVMO) species are high-valent (IV or Ⅴ) electrophilic transition metals with double- or triple-bonded oxygen ligands at the end, such as high-valent iron oxide (Fe Ⅳ =O) species and high-valent cobalt oxide (Co Ⅳ =O) species. Compared with free radicals, HVMO species have longer lifetimes, higher steady-state concentrations, and lower sensitivity to non-target substrates (such as natural organic compounds, inorganic ions, etc.), making them more capable of decomposing pollutants in actual environments. However, the formation of free radicals only requires a single electron transfer between SACs and PMS, while the generation of HVMO requires two or more electron transfers. This poses a challenge to the selective formation of HVMO. In addition, due to the limitations of the "oxygen wall" rule, the d orbitals of late transition metals (e.g., Co, Ni, and Cu, etc.) filled with more valence electrons more obviously repel oxygen ligands, making the M=O fragment unstable, making it difficult to form HVMO. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention aims to provide a single-atom catalyst with oxygen-nitrogen co-doped hollow carbon nanocages as a support carrier, and a preparation method and application thereof. The single-atom catalyst has strong resistance to environmental interference, a wide pH range, high activity, good repeatability, low metal dissolution rate, and will not cause secondary pollution.

[0005] In order to achieve the above-mentioned invention object, the present invention provides the following technical solutions:

[0006] The present invention provides a single-atom catalyst using an oxygen-nitrogen co-doped hollow carbon nanocage as a support carrier, comprising an oxygen-nitrogen co-doped hollow carbon nanocage carrier and a transition metal single atom loaded on the carrier, wherein the transition metal single atom is coordinated in the form of M(NC)2(NO)2.

[0007] The coordination of a single transition metal atom in the form of M(NC)2(NO)2 means that the transition metal atom is coordinated with four N atoms, two of which are coordinated with C, and the other two are coordinated with O.

[0008] According to the above scheme, the single-atom catalyst is prepared by mixing transition metal hydrochloride, 1,10-phenanthroline monohydrate and silicon dioxide@resorcinol formaldehyde copolymer nanospheres (SiO2@RF) with a core-shell structure, and then subjecting the mixture to reflux reaction, rotary evaporation and drying; the obtained solid is ground, pyrolyzed and etched to remove SiO2.

[0009] Preferably, the molar ratio of the transition metal hydrochloride to 1,10-phenanthroline monohydrate is 1:3-5, and the molar mass ratio of the transition metal hydrochloride to SiO2@RF is 0.5mmol:2-4g.

[0010] According to the above scheme, the diameter of the hollow carbon nanocage is 180-280nm.

[0011] According to the above scheme, the transition metal single atom is an iron atom or a cobalt atom.

[0012] The present invention provides a method for preparing a single-atom catalyst using an oxygen-nitrogen co-doped hollow carbon nanocage as a support carrier, comprising the following steps:

[0013] Transition metal hydrochloride, 1,10-phenanthroline monohydrate and silicon dioxide@resorcinol formaldehyde copolymer nanospheres (SiO2@RF) with a core-shell structure are mixed and subjected to reflux reaction, rotary evaporation and drying; the obtained solid is ground, pyrolyzed and etched to remove SiO2 to obtain a single-atom catalyst with oxygen-nitrogen co-doped hollow carbon nanocages as a supporting carrier.

[0014] According to the above scheme, the transition metal hydrochloride is FeCl2·4H2O or CoCl2·6H2O.

[0015] According to the above scheme, the molar ratio of the transition metal hydrochloride to 1,10-phenanthroline monohydrate is 1:3-5, and the amount and mass ratio of the transition metal hydrochloride to SiO2@RF is 0.5mmol:2-4g.

[0016] According to the above scheme, the reflux temperature is 50-70°C, and the reflux time is 3-6h.

[0017] According to the above scheme, the pyrolysis atmosphere is N2, the pyrolysis temperature is 600-800°C, and the pyrolysis time is 2-4h; preferably, the pyrolysis heating rate is 2-10°C / min.

[0018] According to the above scheme, SiO2 is removed by etching with HF solution; preferably, the mass ratio of the HF solution is 3-8wt%, and the etching time is 4-12h.

[0019] According to the above scheme, the method for preparing SiO2@RF nanospheres with a core-shell structure comprises the following steps:

[0020] Water, ethanol and ammonia water are mixed to obtain a mixed solution, tetramethyl orthosilicate (TMOS), formaldehyde aqueous solution and resorcinol are added to the obtained mixed solution in sequence, and the mixture is stirred for reaction, centrifuged, washed and dried to obtain SiO2@RF nanospheres with a core-shell structure.

[0021] Preferably, the volume ratio of water, ethanol and aqueous ammonia is 1:(5-9):(0.2-0.5).

[0022] Preferably, the mass of formaldehyde in the formaldehyde aqueous solution is 37-40% of the total mass of formaldehyde and water.

[0023] Preferably, the ratio of tetramethyl orthosilicate, formaldehyde aqueous solution and resorcinol is: 1 mL: 0.1-0.2 mL: 0.1-0.2 g.

[0024] Preferably, the volume ratio of tetramethyl orthosilicate to the mixed solution of water, ethanol and ammonia water is 1:20-30.

[0025] Preferably, the stirring reaction time is 12-36 hours.

[0026] According to the above scheme, the preparation method has the steps of:

[0027] 1) adding 1,10-phenanthroline monohydrate and SiO2@RF having a core-shell structure to an anhydrous ethanol dispersion of a transition metal hydrochloride, reflux stirring to react, rotary evaporation, and drying to obtain a SiO2@RF@M-phenanthroline complex;

[0028] 2) grinding and pyrolyzing the SiO2@RF@M-phenanthroline complex solid obtained in step 1) to obtain a black powder;

[0029] 3) The black powder obtained in step 2) is etched with HF solution to remove SiO2, thereby obtaining a single-atom catalyst (denoted as HCNCs@M(NC)2(NO)2 catalyst) with oxygen-nitrogen co-doped hollow carbon nanocages as a supporting carrier.

[0030] Preferably, in step 3), the mass ratio of the HF solution is 3-8wt%, and the black powder is stirred in the HF solution for 4-12h.

[0031] The present invention provides application of the above single-atom catalyst in catalytic degradation of organic pollutants.

[0032] The present invention provides a method for catalytic degradation of organic pollutants using a single atom catalyst, comprising the following steps:

[0033] A single-atom catalyst supported by oxygen-nitrogen co-doped hollow carbon nanocages was added to wastewater containing organic pollutants for adsorption saturation, and then persulfate (PMS) was added to induce the catalytic degradation reaction of the pollutants.

[0034] According to the above scheme, the pollutant concentration is 10-100 μM.

[0035] According to the above scheme, the pollutants are pollutants containing electron-donating groups such as bisphenol A (BPA), phenol (PE), 4-chlorophenol (4-CP), 2,4-dichlorophenol (2,4-DCP), and pollutants containing electron-withdrawing groups such as p-nitrophenol (PNP), p-nitrobenzaldehyde (PNBD), and p-nitrobenzyl alcohol (PNBA).

[0036] According to the above scheme, the pH of wastewater containing organic pollutants is 2-10.

[0037] According to the above scheme, the concentration of the single-atom catalyst in the wastewater containing organic pollutants is 0.01-0.1 mg / mL, the concentration of the PMS in the wastewater containing organic pollutants is 50 μM-3 mM, and the catalytic degradation time is 0.5-50 min.

[0038] According to the above scheme, the adsorption time is 5-10min.

[0039] The invention provides a single-atom catalyst with an oxygen-nitrogen co-doped hollow carbon nanocage as a support carrier. Oxygen doping changes the coordination environment of nitrogen-doped metal-based single-atom catalysts (SACs), so that the coordination form of the metal center changes from M-N4 to M(NC)2(NO)2, and the strong electronegativity of the oxygen atom reduces the electron density of the metal center, that is, reduces the metal d orbital electron filling, helps to reduce the metal's rejection of terminal oxygen ligands, so that the M=O fragment can exist stably, so that in the catalytic degradation reaction of pollutants induced by PMS, the single-atom catalyst can form HVMO species by receiving electrons from the terminal oxygen ligands; the formation of HVMO ensures that the single-atom catalyst / PMS system can achieve efficient removal of various toxic substances in a harsh reaction environment.

[0040] In addition, the present invention uses SiO2@RF as a macroporous pore former and carbon / oxygen template, directly loads the complex formed by transition metal hydrochloride and 1,10-phenanthroline monohydrate, and finally pyrolyzes and etches SiO2 to obtain a single-atom catalyst with oxygen-nitrogen co-doped hollow carbon nanocage as a support carrier; on the one hand, the transition metal hydrochloride and 1,10-phenanthroline monohydrate are mixed with SiO2@RF in advance, and during the pyrolysis and carbonization process, the transition metal forms M(NC)2(NO)2 coordination with N and O, effectively avoiding the loss of oxygen during the pyrolysis and carbonization process, making M(NC)2(NO)2 coordination possible. On the other hand, since the surface free energy of the transition metal increases significantly with the decrease of its particle size, isolated single metal atoms are highly unstable in thermodynamics and tend to aggregate. Therefore, in order to obtain a more stable structure during the pyrolysis process, the metal atoms will not only form a new coordination environment, but also aggregate to form metal particles or clusters. Using SiO2 as a hard template can provide a stable environment and limit the migration of metal atoms to a certain extent, thereby helping to maintain the high dispersion of metal single atom catalysts and the exposure of active sites, further improving their catalytic performance.

[0041] Beneficial effects of the present invention:

[0042] 1. The present invention provides a single-atom catalyst with oxygen-nitrogen co-doped hollow carbon nanocages as a supporting carrier, the coordination of the metal center is M(NC)2(NO)2, and the unique coordination structure is conducive to the formation of HVMO species in the catalyst process, thereby achieving efficient removal of various toxic substances, and the pollutants can be completely degraded in as fast as 30 seconds; the pH application range is wide, and efficient catalysis can be achieved in the pH range of 2-10; at the same time, the single-atom catalyst also has excellent stability and reusability, low cost, low energy consumption, low metal dissolution rate, no secondary pollution, and is easy to operate and easy to use, and has great application potential in sewage treatment.

[0043] 2. The present invention provides a method for preparing a single-atom catalyst with an oxygen-nitrogen co-doped hollow carbon nanocage as a supporting carrier, wherein SiO2@RF is used as a template to directly load a complex formed by a metal hydrochloride and 1,10-phenanthroline monohydrate, and finally SiO2 is pyrolyzed and etched; oxygen loss is effectively avoided, which is beneficial to the formation of an M(NC)2(NO)2 coordination structure, and at the same time, the SiO2 hard template is beneficial to pyrolysis to obtain highly dispersed metal single atoms; the preparation process is simple and the conditions are mild, and the obtained single-atom catalyst has a high-efficiency removal effect on different pollutants, a wide pH applicable range, and a broad prospect for industrial application.

[0044] 3. The present invention applies the obtained single-atom catalyst to the catalytic degradation reaction of pollutants induced by PMS. Only a relatively low concentration of PMS is needed to generate sufficient active oxygen species, thereby achieving efficient degradation of various pollutants, greatly reducing resource consumption and residual sulfate ions, and being green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a flow chart for preparing the single-atom catalyst using the oxygen-nitrogen co-doped hollow carbon nanocage as a supporting carrier as described in Examples 1 and 2.

[0046] Figure 2 a is a field emission scanning electron micrograph of the HCNCs@Fe(NC)2(NO)2 single atom catalyst described in Example 1, Figure 2 b is the particle size distribution diagram of the HCNCs@Fe(NC)2(NO)2 single atom catalyst described in Example 1, Figure 2 c is an aberration-corrected high-angle annular dark-field scanning transmission electron microscope image of the HCNCs@Fe(NC)2(NO)2 single-atom catalyst described in Example 1, Figure 2 d shows the particle size distribution of Fe in HCNCs@Fe(NC)2(NO)2 single atom catalyst.

[0047] Figure 3 It is the synchrotron radiation data image of the HCNCs@Fe(NC)2(NO)2 single atom catalyst and other iron-containing catalysts described in Example 1; wherein Figure 3 a is the X-ray absorption near-edge structure image of Fe atoms in different catalysts. Figure 3 b is the Fourier transform k of Fe atoms in HCNCs@Fe(NC)2(NO)2 3 Weighted extended X-ray absorption fine structure data and their quantitative least squares fitting, Figure 3 c is the coordination structure of HCNCs@Fe(NC)2(NO)2.

[0048] Figure 4It is the synchrotron radiation data image of the HCNCs@Co(NC)2(NO)2 single atom catalyst and other iron-containing catalysts described in Example 2; wherein Figure 4 a is the X-ray absorption near-edge structure image of Co atoms in different catalysts. Figure 4 b is the Fourier transform k of Co atom in HCNCs@Co(NC)2(NO)2 3 Weighted extended X-ray absorption fine structure data and their quantitative least squares fitting, Figure 4 c is the coordination structure of HCNCs@Co(NC)2(NO)2.

[0049] Figure 5 This is a curve diagram of the catalytic degradation of BPA by HCNCs@Fe(NC)2(NO)2 described in Application Example 1.

[0050] Figure 6 This is a curve diagram of the catalytic degradation of BPA by HCNCs@Co(NC)2(NO)2 described in Application Example 2.

[0051] Figure 7 It is the contribution of various active oxygen species when HCNCs@Fe(NC)2(NO)2 catalyzes the degradation of BPA described in Application Example 3; the small figure is the fitting data of pseudo-first-order kinetics when HCNCs@Fe(NC)2(NO)2 catalyzes the degradation of BPA under different quenchers.

[0052] Figure 8 It is the contribution of various active oxygen species when HCNCs@Co(NC)2(NO)2 catalyzes the degradation of BPA described in Application Example 4; the small figure is the fitting data of pseudo-first-order kinetics when HCNCs@Co(NC)2(NO)2 catalyzes the degradation of BPA under different quenchers.

[0053] Fig. 9 a is that oxygen doping as described in Application Example 5 effectively improves the catalytic performance of HCNCs@Fe(NC)2(NO)2, Fig. 9 b is that oxygen doping effectively increases the Fe IV =O's contribution to the system's degradation of BPA.

[0054] Fig.10 The oxygen doping described in Application Example 6 effectively solves the problem that late transition metal Co-based SACs are difficult to produce Co during catalytic oxidation. IV =O problem.

[0055] Fig.11 is a curve diagram of the catalytic degradation of different pollutants by HCNCs@Fe(NC)2(NO)2 described in Application Example 7; wherein Fig.11a is the degradation curve of phenol (PE), 4-chlorophenol (4-CP), and 2,4-dichlorophenol (2,4-DCP) containing electron-donating groups. Fig.11 b is the degradation curves of p-nitrophenol (PNP), p-nitrobenzaldehyde (PNBD), and p-nitrobenzyl alcohol (PNBA) containing electron-withdrawing groups.

[0056] Fig.12 This is a curve chart of the catalytic degradation of BPA by the HCNCs@Fe(NC)2(NO)2 single atom catalyst described in Application Example 8 under different pH conditions.

[0057] Fig.13 This is a curve chart of the catalytic degradation of BPA by the HCNCs@Fe(NC)2(NO)2 single atom catalyst described in Application Example 9 in simulated water samples and actual water samples.

[0058] Fig.14 This is a comparison of the catalytic effects of the HCNCs@Fe(NC)2(NO)2 single atom catalyst described in Application Example 10 and other catalysts.

[0059] Fig.15 This is a diagram of the HCNCs@Fe(NC)2(NO)2 / mixed cellulose ester (MCE) membrane continuous flow pollutant degradation device in Application Example 11.

[0060] Fig.16 a is the change in catalytic performance of the HCNCs@Fe(NC)2(NO)2 / MCE composite microfiltration membrane in Application Example 11 during continuous use for 500 h. Fig.16 b is the dissolution diagram of metal Fe during the continuous use of 500 hours. DETAILED DESCRIPTION

[0061] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0062] Comparative Example 1 Preparation of Iron Nanoparticles

[0063] 0.5mmol FeCl2·4H2O and 2mmol 1,10-phenanthroline monohydrate were added to 60mL anhydrous ethanol, and after ultrasonic dispersion, the mixture was refluxed at 60℃ for 4h, and then rotary evaporated and dried to obtain Fe(phen)x; the Fe(phen)x solid was ground, heated to 700℃ at a rate of 2℃ / min in N2 atmosphere, and then pyrolyzed for 2h; the black solid obtained after pyrolysis was dispersed in 100mL 5wt% HF; the etching process was repeated three times; then, the solid was repeatedly washed with a large amount of ultrapure water until the filtrate reached a neutral pH. Finally, the iron nanoparticle (FeNPs) catalyst was obtained by drying at 60℃ and grinding.

[0064] Comparative Example 2 Preparation of HCNCs@NC without transition metal

[0065] (1) Synthesis of SiO2@RF nanospheres: 10 mL of ultrapure water, 70 mL of anhydrous ethanol and 3 mL of aqueous ammonia were stirred together at room temperature for 10 min. Subsequently, 3.5 mL of TMOS was quickly added to the above solution and stirring continued for 15 min. Next, 0.56 mL of formaldehyde aqueous solution (37 wt%) and 0.4 g of resorcinol were added and stirred at 25 °C for 24 h. The orange-yellow precipitate was collected by centrifugation and washed several times with ethanol and water. Finally, SiO2@RF nanospheres were obtained by drying at 60 °C.

[0066] (2) Preparation of HCNCs@NC: 2 mmol of 1,10-phenanthroline monohydrate was added to 60 mL of anhydrous ethanol, and 3 g of SiO2@RF was added after ultrasonic dispersion. The mixture was refluxed at 60 °C and stirred for 4 h. SiO2@RF@phen was then obtained by rotary evaporation and drying. The SiO2@RF@phen solid was ground and heated to 700 °C at a rate of 2 °C / min in a N2 atmosphere and then pyrolyzed for 2 h. The black solid obtained after pyrolysis was dispersed in 100 mL of 5 wt% HF and stirred at room temperature for 4 h to etch SiO2. The etching process was repeated three times. Subsequently, the solid was repeatedly washed with a large amount of ultrapure water until the filtrate reached a neutral pH. Finally, the HCNCs@NC catalyst was obtained by drying and grinding at 60 °C.

[0067] Comparative Example 3 Preparation of oxygen-free doped M-N4-C

[0068] The present invention prepares SiO2 nanospheres by a one-pot method, uses the nanospheres as macroporous pore formers and templates, and then prepares oxygen-free doped M-N4-C catalysts by a pyrolysis method, which specifically includes the following steps:

[0069] (1) Synthesis of SiO2 nanospheres: 10 mL of ultrapure water, 70 mL of anhydrous ethanol, and 5 mL of aqueous ammonia were stirred together at room temperature for 10 min. Subsequently, 3.5 mL of TMOS was quickly added to the above solution and stirred for 15 min and at 25 °C for 24 h. The white precipitate was collected by centrifugation and washed several times with ethanol and water. Finally, the SiO2 nanospheres were dried at 60 °C.

[0070] (2) Preparation of M-N4-C: 0.5 mmol of metal hydrochloride was added to 60 mL of anhydrous ethanol, and 2 mmol of 1,10-phenanthroline monohydrate was added after ultrasonic dispersion. After ultrasonic dispersion again, 3 g of SiO2 was added, and the mixture was refluxed at 60 °C for 4 h. Then, SiO2@M(phen) was obtained by rotary evaporation and drying. x ; SiO2@M(phen) x The solid was ground and heated to 700°C in a N2 atmosphere at a rate of 2°C / min and then pyrolyzed for 2h. The black solid obtained after pyrolysis was dispersed in 100mL of 5 wt% HF and stirred at room temperature for 4h to etch SiO2. The etching process was repeated three times. Subsequently, the solid was repeatedly washed with a large amount of ultrapure water until the filtrate reached a neutral pH. Finally, the oxygen-free doped M-N4-C catalyst was obtained by drying at 60°C and grinding.

[0071] The metal hydrochloride in step (2) is FeCl2·4H2O or CoCl2·6H2O.

[0072] Example 1 Preparation of HCNCs@Fe(NC)2(NO)2

[0073] In this example, SiO2@RF nanospheres were prepared by a one-pot method and used as macroporous pore formers and carbon / oxygen templates. HCNCs@Fe(NC)2(NO)2 were then prepared by thermal decomposition. The preparation process is as follows: Figure 1 , specifically including the following steps:

[0074] (1) SiO2@RF copolymer nanospheres were prepared according to the method of step (1) of comparative example 2.

[0075] (2) Synthesis of HCNCs@Fe(NC)2(NO)2: 0.5 mmol FeCl2·4H2O was added to 60 mL anhydrous ethanol, and 2 mmol 1,10-phenanthroline monohydrate was added after ultrasonic dispersion. After ultrasonic dispersion again, 3 g SiO2@RF obtained in step (1) was added, and the mixture was refluxed at 60°C for 4 h, and then rotary evaporated and dried to obtain SiO2@RF@Fe(phen) x ; SiO2@RF@Fe(phen) xThe solid was ground and heated to 700℃ in N2 atmosphere at a rate of 2℃ / min and then pyrolyzed for 2h. The black solid obtained after pyrolysis was dispersed in 100mL 5wt% HF and stirred at room temperature for 4h to etch SiO2. The etching process was repeated three times. Subsequently, the solid was repeatedly washed with a large amount of ultrapure water until the filtrate reached a neutral pH. Finally, a single-atom catalyst supported by oxygen-nitrogen co-doped hollow carbon nanocages was obtained by drying and grinding at 60℃, which was recorded as HCNCs@Fe(NC)2(NO)2 single-atom catalyst.

[0076] Figure 2 a shows the hollow carbon nanocage morphology of HCNCs@Fe(NC)2(NO)2 single atom catalyst. Figure 2 b shows the size distribution of the carbon nanocages 180nm-280nm, with an average particle size of 236nm±19nm. Figure 2 a and Figure 2 b proves that the single-atom catalyst is a single-atom catalyst supported in a hollow carbon nanocage. Figure 2 c shows the monodisperse state of Fe in the HCNCs@Fe(NC)2(NO)2 single atom catalyst. Figure 2 d shows the particle size distribution of Fe in the HCNCs@Fe(NC)2(NO)2 single atom catalyst, where the average particle size of Fe is Figure 2 and 2 d proves that Fe in HCNCs@Fe(NC)2(NO)2 is dispersed in single atom.

[0077] Example 2 Preparation of HCNCs@Co(NC)2(NO)2

[0078] In this example, SiO2@RF nanospheres were prepared by a one-pot method and used as macroporous pore formers and carbon / oxygen templates. HCNCs@Co(NC)2(NO)2 were then prepared by thermal decomposition. The preparation process is as follows: Figure 1 , specifically including the following steps:

[0079] (1) SiO2@RF copolymer nanospheres were prepared according to the method of step (1) of comparative example 2.

[0080] (2) Synthesis of HCNCs@Co(NC)2(NO)2: 0.5 mmol CoCl2·6H2O was added to 60 mL anhydrous ethanol, and 2 mmol 1,10-phenanthroline monohydrate was added after ultrasonic dispersion. After ultrasonic dispersion again, 3 g SiO2@RF obtained in step (1) was added, and the mixture was refluxed at 60°C for 4 h, and then rotary evaporated and dried to obtain SiO2@RF@Co(phen)x ; SiO2@RF@Co(phen) x The solid was ground and heated to 700℃ in N2 atmosphere at a rate of 2℃ / min and then pyrolyzed for 2h. The black solid obtained after pyrolysis was dispersed in 100mL 5wt% HF and stirred at room temperature for 4h to etch SiO2. The etching process was repeated three times. Subsequently, the solid was repeatedly washed with a large amount of ultrapure water until the filtrate reached a neutral pH. Finally, a single-atom catalyst supported by oxygen-nitrogen co-doped hollow carbon nanocages was obtained by drying and grinding at 60℃, which was recorded as HCNCs@Co(NC)2(NO)2 single-atom catalyst.

[0081] Figure 3 and Figure 4 It shows that oxygen doping reduces the electron density of metal in HCNCs@M(NC)2(NO)2 and the coordination form of metal atoms is M(NC)2(NO)2. The above results prove the successful preparation of HCNCs@M(NC)2(NO)2.

[0082] Application Example 1 Degradation of BPA by HCNCs@Fe(NC)2(NO)2

[0083] The oxygen-doped HCNCs@Fe(NC)2(NO)2 single-atom catalyst prepared in Example 1 was added to a 10 mM sodium borate-boric acid buffer solution containing BPA at pH = 7, and after adsorption for 10 minutes, PMS was added to induce the catalytic degradation reaction of the pollutants. In the reaction, the concentration of BPA was 50 μM, the concentration of the single-atom catalyst was 0.1 mg / mL, the concentration of PMS was 400 μM, and the catalytic degradation time was 120 s.

[0084] Figure 5 It is a curve diagram of HCNCs@Fe(NC)2(NO)2 catalytic degradation of BPA in Application Example 1; Figure 5 It was shown that HCNCs@Fe(NC)2(NO)2 could achieve complete degradation of BPA within 30 s, proving that HCNCs@Fe(NC)2(NO)2 had ultra-high catalytic activity.

[0085] Application Example 2 Degradation of BPA by HCNCs@Co(NC)2(NO)2

[0086] Same as Application Example 1, the single atom catalyst was changed to HCNCs@Co(NC)2(NO)2 prepared in Example 2, the concentration of PMS in the degradation mixture was changed to 100 μM, and the other conditions were the same as Application Example 1.

[0087] Figure 6It is a curve diagram of HCNCs@Co(NC)2(NO)2 catalytic degradation of BPA in Application Example 2; Figure 6 It shows that HCNCs@Co(NC)2(NO)2 can achieve complete degradation of BPA within 45s, proving that HCNCs@Co(NC)2(NO)2 has ultra-high catalytic activity.

[0088] Application Example 3 Contribution of various active oxygen species in HCNCs@Fe(NC)2(NO)2 catalytic degradation of BPA

[0089] The single-atom catalyst prepared in Example 1 was added to wastewater containing BPA and a quencher. After adsorption for 10 minutes, PMS was added to induce the catalytic degradation reaction of the pollutants. The quencher was selected according to the active oxygen species to be quenched; superoxide radicals (O2 .- ) when the quencher is superoxide dismutase (SOD); quenching sulfate radicals (SO4 ·- ) and hydroxyl radicals (·OH), the quencher is methanol (MeOH); quenching sulfate radicals (SO4 ·- ) when the quenching agent is tert-butyl alcohol (TBA); quenching high-valent iron oxide (Fe IV =O) species, the quencher is benzyl sulfoxide (PMSO), the final concentration of each substance in the degradation reaction is adjusted with 10mM sodium borate-boric acid buffer solution with pH=7, the BPA concentration in the degradation reaction is 50μM, the concentration of the single atom catalyst in the degradation reaction is 0.05mg / mL, the concentration of PMS in the degradation reaction is 400μM, the concentration of SOD in the degradation reaction is 100U / mL, the concentration of MeOH or TBA in the degradation reaction is 400mM, the concentration of PMSO in the degradation reaction is 4mM or 40mM, and the catalytic degradation time is 120s.

[0090] Figure 7 The contribution of various active oxygen species in the catalytic degradation of BPA by HCNCs@Fe(NC)2(NO)2 was shown. IV =O is the main active species in the degradation of BPA by HCNCs@Fe(NC)2(NO)2 / PMS system.

[0091] Application Example 4 Contribution of various active oxygen species in HCNCs@Co(NC)2(NO)2 catalytic degradation of BPA

[0092] Similar to Application Example 3, the contribution of each active oxygen species in the catalytic degradation of BPA by HCNCs@Co(NC)2(NO)2 prepared in Example 2 was investigated. The active oxygen species included O2 ·- 、SO4·- , OH, Fe IV =O species. The experimental conditions are consistent with those of Application Example 3 except for the following points. The different experimental conditions are as follows: the concentration of the single atom catalyst in the degradation reaction is 0.1 mg / mL, the concentration of PMS in the degradation reaction is 100 μM, the concentration of MeOH or TBA in the degradation reaction is 100 mM, and the concentration of PMSO in the degradation reaction is 10 mM.

[0093] Figure 8 The contribution of various reactive oxygen species in the catalytic degradation of BPA by HCNCs@Co(NC)2(NO)2 is shown. The reactive oxygen species include O2 ·- 、SO4 ·- , OH, high-valent cobalt oxide (Co IV =O) species. The experimental results show that Co IV =O is the main active species in the degradation of BPA by HCNCs@Fe(NC)2(NO)2 / PMS system.

[0094] Application Example 5 Differences between HCNCs@Fe(NC)2(NO)2 and Fe-N4-C in catalytic degradation of BPA

[0095] Comparison of activity differences: When degrading BPA, the single-atom catalysts used were HCNCs@Fe(NC)2(NO)2 prepared in Example 1 and Fe-N4-C prepared in Comparative Example 3. The catalyst concentration in the degradation experiment was 0.05 mg / mL, and the other experimental conditions were consistent with those in Application Example 1.

[0096] Comparison of active species differences: Same as Application Example 3. Using PMSO as the quencher, the Fe IV =O's contribution to the system.

[0097] Fig. 9 It shows that oxygen doping effectively improves the catalytic performance of HCNCs@Fe(NC)2(NO)2 and increases the Fe IV =O's contribution to the system's degradation of BPA.

[0098] Application Example 6 Differences between HCNCs@Co(NC)2(NO)2 and Co-N4-C in catalytic degradation of BPA

[0099] Comparison of activity differences: When degrading BPA, the single-atom catalysts used were HCNCs@Co(NC)2(NO)2 prepared in Example 2 and Co-N4-C prepared in Comparative Example 3. The remaining experimental conditions were consistent with those in Application Example 2.

[0100] Comparison of active species differences: Same as Application Example 4. Using MeOH as the quencher, the contribution of free radicals to the system was investigated when oxygen-doped HCNCs@Co(NC)2(NO)2 and oxygen-free Co-N4-C were used as catalysts.

[0101] Fig.10 It shows that when oxygen-doped HCNCs@Co(NC)2(NO)2 is used as a catalyst, free radicals are not the main active species, while when oxygen-free Co-N4-C is used as a catalyst, free radicals are the main active species. Combined with Application Example 4, it shows that oxygen doping effectively solves the problem that late transition metal Co-based SACs are difficult to produce Co during catalytic oxidation. IV =O problem.

[0102] Application Example 7 Degradation of other organic pollutants by HCNCs@Fe(NC)2(NO)2

[0103] The single-atom catalyst prepared in Example 1 was adsorbed in wastewater containing organic pollutants for 10 minutes, and then PMS was added to induce the catalytic degradation reaction of the pollutants. The pollutants were PE, 4-CP, 2,4-DCP, PNP, PNBD, and PNBA. The concentration of the pollutants in the degradation reaction was 20 μM, the concentration of the single-atom catalyst in the degradation reaction was 0.05 mg / mL, the concentration of PMS in the degradation reaction of the three electron-donating group pollutants of PE, 4-CP, and 2,4-DCP was 400 μM, and the catalytic degradation time was 2 minutes. The concentration of PMS in the degradation reaction of the three electron-withdrawing group pollutants of PNP, PNBD, and PNBA was 3 mM, of which the catalytic degradation time of PNP was 20 minutes, and the catalytic degradation time of PNBD and PNBA was 50 minutes.

[0104] Fig.11 The degradation performance of HCNCs@Fe(NC)2(NO)2 on different pollutants was shown, proving the efficient removal of various toxic substances by HCNCs@Fe(NC)2(NO)2.

[0105] Application Example 8 catalytic degradation of BPA under different pH conditions based on HCNCs@Fe(NC)2(NO) single atom catalyst.

[0106] The oxygen-doped HCNCs@Fe(NC)2(NO)2 single-atom catalyst prepared in Example 1 was added to a 10 mM sodium borate-boric acid buffer solution containing BPA. After adsorption for 10 minutes, PMS was added to induce the catalytic degradation reaction of the pollutants. The pH value of the sodium borate-boric acid buffer solution is selected according to the conditions required for the experiment. In the reaction, the concentration of BPA is 50 μM, the concentration of the single-atom catalyst is 0.05 mg / mL, and the concentration of PMS is 400 μM. The removal rate is detected at catalytic degradation times of 90 s and 120 s, respectively.

[0107] Fig.12 The catalytic performance of HCNCs@Fe(NC)2(NO)2 single atom catalysts in the degradation of BPA was compared in the range of pH = 2-10. The experimental results show that the catalytic performance of HCNCs@Fe(NC)2(NO)2 single atom catalysts is not affected by pH value.

[0108] Application Example 9: Application of HCNCs@Fe(NC)2(NO)2 single atom catalyst in the removal of BPA from actual wastewater

[0109] All places where water is needed are replaced with corresponding water samples according to experimental requirements. The catalyst concentration in the degradation experiment is 0.05 mg / mL, and the remaining conditions are used to carry out the catalytic degradation experiment according to Application Example 1.

[0110] Fig.13 The performance of HCNCs@Fe(NC)2(NO)2 in catalytic degradation of BPA in simulated water samples and three real water samples was compared. The simulated water sample was ultrapure water, and the real water samples were water from East Lake, Yangtze River, and tap water. The experimental results show that HCNCs@Fe(NC)2(NO)2 can achieve efficient removal of organic pollutants in real water sample environments and has the potential for practical applications.

[0111] Application Example 10 Comparison of BPA degradation ability of HCNCs@Fe(NC)2(NO)2, FeNPs, HCNCs@NC, and commercial Fe3O4

[0112] The type of catalyst used was changed according to the experimental needs, and the catalytic degradation experiment was carried out according to Application Example 1. The catalysts were HCNCs@Fe(NC)2(NO)2 prepared in Example 1 of the present invention, FeNPs catalyst prepared in Comparative Example 1, HCNCs@NC catalyst prepared in Comparative Example 2, and commercial Fe3O4 catalyst.

[0113] Fig.14It is shown that the catalytic effect of HCNCs@Fe(NC)2(NO)2 is much higher than that of FeNPs, HCNCs@NC, and commercial Fe3O4 catalysts, which indicates that the unique Fe(NC)2(NO)2 coordination form and the full exposure of metal active sites significantly improve the catalytic activity of the catalyst.

[0114] Application Example 11 Continuous flow pollutant degradation device based on HCNCs@Fe(NC)2(NO)2 / mixed cellulose ester (MCE) membrane and its application

[0115] The HCNCs@Fe(NC)2(NO)2 prepared in Example 1 was used to construct a composite membrane continuous flow pollutant degradation device, the device being as Fig.15 The constant flow injection system, premixing chamber and reactor are shown; the constant flow injection system includes a constant flow injection pump and two 50mL syringes, the syringes are respectively filled with pollutant solution and PMS solution; the premixing chamber is a filter with an inner diameter of 25mm; the reactor contains a filter with an inner diameter of 25mm and a HCNCs@Fe(NC)2(NO)2 / MCE composite membrane, the composite membrane is an MCE membrane deposited with 20mg HCNCs@Fe(NC)2(NO)2, the pore size of the MCE membrane is 0.45μm and the diameter is 25mm; wherein, a 1 / 16 inch polyetheretherketone (PEEK) tube, a 1 / 16PEEK connector and a Luer connector are used to connect the flow path of the entire system, and a beaker is used to receive the aqueous solution purified by the continuous flow system. The constant flow injection pump can provide power to continuously pump the pollutant solution and the PMS solution from the syringe through the premixing chamber into the reactor and finally into the beaker. The purpose of the premixing chamber is to mix the pollutant solution and PMS solution in the two flow paths; the continuous flow pollutant degradation means that the mixed solution can spontaneously achieve PMS activation, HVMO species generation, pollutant degradation and separation of water and catalyst during the process of passing through the reactor. The whole process is carried out continuously without pausing to provide additional time for the reaction in the reactor.

[0116] Fig.16 The changes in the catalytic performance of the HCNCs@Fe(NC)2(NO)2 / MCE composite microfiltration membrane during continuous use for 500 hours and the dissolution of metal Fe during the process are shown. The experimental results show that the HCNCs@Fe(NC)2(NO)2 / MCE system has good stability in the 500-hour continuous flow reaction, low metal dissolution rate, and will not cause secondary pollution.

[0117] Obviously, the above comparative examples, embodiments and application examples are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the invention.

Claims

1. A single-atom catalyst using oxygen-nitrogen co-doped hollow carbon nanocages as a support carrier, characterized in that: It comprises an oxygen-nitrogen co-doped hollow carbon nano cage carrier and a transition metal single atom loaded on the carrier; the transition metal single atom is coordinated in the form of M(NC)2(NO)2.

2. The single atom catalyst according to claim 1, characterized in that The transition metal single atom is an iron atom or a cobalt atom.

3. A method for preparing a single-atom catalyst using oxygen-nitrogen co-doped hollow carbon nanocages as a support carrier as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: The transition metal hydrochloride, 1,10-phenanthroline monohydrate and silicon dioxide@resorcinol formaldehyde copolymer nanospheres with a core-shell structure are mixed and subjected to reflux reaction, rotary evaporation and drying; the obtained solid is ground, pyrolyzed and etched to remove SiO2 to obtain a single-atom catalyst with oxygen-nitrogen co-doped hollow carbon nanocages as a supporting carrier.

4. The preparation method according to claim 3, characterized in that: The reflux temperature is 50-70°C, and the reflux time is 3-6h; the pyrolysis atmosphere is N2, the pyrolysis temperature is 600-800°C, and the pyrolysis time is 2-4h.

5. The preparation method according to claim 3, characterized in that: The molar ratio of transition metal hydrochloride to 1,10-phenanthroline monohydrate is 1:3-5, and the molar mass ratio of the transition metal hydrochloride to the silicon dioxide@resorcinol formaldehyde copolymer nanospheres with a core-shell structure is 0.5mmol:2-4g.

6. The preparation method according to claim 3, characterized in that: The specific steps are: 1) adding 1,10-phenanthroline monohydrate and silicon dioxide@resorcinol formaldehyde copolymer nanospheres with a core-shell structure to an anhydrous ethanol dispersion of a transition metal hydrochloride, reflux stirring to react, rotary evaporation, and drying to obtain a SiO2@RF@M-phenanthroline complex; 2) grinding and pyrolyzing the SiO2@RF@M-phenanthroline complex solid obtained in step 1) to obtain a black powder; 3) The black powder obtained in step 2) is etched with HF solution to remove SiO2, thereby obtaining a single-atom catalyst with oxygen-nitrogen co-doped hollow carbon nanocage as a supporting carrier.

7. The preparation method according to claim 3 or 6, characterized in that: The method for preparing the silicon dioxide@resorcinol formaldehyde copolymer nanospheres having a core-shell structure comprises the following steps: Water, ethanol and ammonia water are mixed to obtain a mixed solution, tetramethyl orthosilicate, formaldehyde aqueous solution and resorcinol are added to the obtained mixed solution in sequence, and the mixture is stirred for reaction, centrifuged, washed and dried to obtain silicon dioxide@resorcinol formaldehyde copolymer nanospheres with a core-shell structure.

8. Use of the single atom catalyst as claimed in any one of claims 1 to 2 in catalytic degradation of organic pollutants.

9. A method for catalytic degradation of organic pollutants using a single atom catalyst as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: A single-atom catalyst supported by oxygen-nitrogen co-doped hollow carbon nanocages was added to wastewater containing organic pollutants for adsorption saturation, and then persulfate was added to induce the catalytic degradation reaction of the pollutants.

10. The method according to claim 9, characterized in that The concentration of the single-atom catalyst in wastewater containing organic pollutants is 0.01-0.1 mg / mL; the concentration of the PMS in wastewater containing organic pollutants is 50 μM-3 mM; the catalytic degradation time is 0.5-50 min; and the pH of the wastewater containing organic pollutants is 2-10.

Citation Information

Cited By

  • Binary single-site material for controlling spatial distribution of active sites, preparation method and application

    CN120714629A

  • Preparation method and application of copper-doped empty-shell multi-pore-channel nanosphere advanced oxidation water treatment catalyst

    CN121551067A

  • Preparation method and application of copper-doped hollow porous nanosphere advanced oxidation water treatment catalyst

    CN121551067B

  • Electrochemical sensor based on monatomic catalyst and method for detecting scutellarin

    CN122377513A

  • Nitrogen-oxygen co-coordinated iron monatomic catalyst, preparation method thereof and application of nitrogen-oxygen co-coordinated iron monatomic catalyst in degradation of phenolic pollutants

    CN122424852A